Listeria monocytogenes contamination in chicken offal at wet market and supermarket - Huat, J.T.Y.; Wai, G.Y.; Nor Khaizura, Mahmud @ Abdul Rashid; Son, Radu (2021)
Listeria monocytogenes is a foodborne pathogen that cause serious illness in vulnerable individuals such as infant, pregnant woman, elderly and immunocompromised patient. This study aimed to determine the prevalence of L. monocytogenes in chicken offal samples between wet market and supermarket. A total of 428 chicken offal samples (chicken gizzard=154, heart=131, liver=143) from wet markets and supermarkets in Klang Valley, Malaysia were examined using multiplex polymerase chain reaction (PCR) assay and conventional plating method. Both PCR assay and plating method are equally reliable in detecting the presence of L. monocytogenes in chicken offal. The prevalence of Listeria spp. and L. monocytogenes from total samples was 8.9% and 6.5%, respectively. L. monocytogenes in chicken offal was found gizzard, liver, and heart at 10.4%, 7.0%, and 1.5%, respectively. L. monocytogenes contamination in samples from supermarkets was significantly higher than those in wet markets which might due to the pathogen psychrophilic characteristic. It can be concluded that refrigerated samples have higher prevalence of L. monocytogenes contamination.